Teamwork and Adherence to Recommendations Explain the Effect of a Care Pathway on Reduced 30-day Readmission for Patients with a COPD Exacerbation. (4th March 2018) - Seys, Deborah; Bruyneel, Luk; Sermeus, Walter; Lodewijckx, Cathy; Decramer, Marc; Deneckere, Svin; Panella, Massimiliano; Vanhaecht, Kris
ABSTRACT: This study aimed to increase our understanding of processes that underlie the effect of care pathway implementation on reduced 30-day readmission rate. Adherence to evidence-based recommendations, teamwork and burnout have previously been identified as potential mechanisms in this association. We conducted a secondary data analysis of 257 patients admitted with chronic obstructive pulmonary disease exacerbation and 284 team members caring for these patients in 19 Belgian, Italian and Portuguese hospitals. Clinical measures included 30-day readmission and adherence to a specific set of five care activities. Teamwork measures included team climate for innovation, level of organized care and burnout (emotional exhaustion, level of competence and mental detachment). Care pathway implementation was significantly associated with better adherence and reduced 30-day readmission. Better adherence and higher level of competence were also related to reduced 30-day readmission. Only better adherence fully mediated the association between care pathway implementation and reduced 30-day readmission. Better team climate for innovation and level of organized care, although both improved after care pathway implementation, did not show any explanatory mechanisms in the association between care pathway implementation and reduced 30-day readmission. Implementation of a care pathway had an impact on clinical and team indicators. To reduce 30-day readmission rates, in the development and implementation of a care pathway, hospitals should measure adherence to evidence-based recommendations during the whole process, as this can give information regarding the success of implementation